Strengthening psychological well-being of Indonesian females with breast cancer through the religious-based caring program: A quasi-experimental study among Muslim population - Komariah, Maria; Agustina, Hana Rizmadewi; Rahayuwati, Laili; Kurniawan, Kurniawan; Gartika, Nina; Mago, Arpit; Qadous, Shurouq Ghalib; Maulana, Sidik (Belitung Raya Foundation, Indonesia, 2024)
Background: Breast cancer presents significant psychological challenges along with physical health concerns, particularly in settings where cultural and spiritual values play a critical role in patient care. Objective: This study aimed to investigate the effect of a religious caring program on the psychological well-being of Indonesian females with breast cancer. Methods: This was a quasi-experimental study with a pretest and posttest control group design, conducted from January to July 2019 at a chemotherapy unit in Bandung, Indonesia. The patients with breast cancer were assigned to the experimental group (n = 55) and the control group (n = 57). Data were collected using the Psychological Well-Being Scale before and three weeks after the intervention. The data were analyzed using independent t-test and ANCOVA (Analysis of Covariance). Results: There was a significant improvement in the mean psychological well-being score in the experimental group following the intervention compared to the control group, with the experimental group showing a significantly higher mean score (Cohen’s d = 1.4548, p <0.001). None of the covariates significantly affected psychological well-being among the experimental group (p >0.05). Conclusion: These results indicate that a religion-based caring program enhances psychological well-being. Thus, the program was effective and particularly well-suited for clinical nurses, suggesting that it should be recommended for Indonesian females with breast cancer to promote their recovery.